Legal Interpretation of Insurance Policies in Dispute Resolution: A Study of Decision No. 247/Pdt.G/2022/PN Bks - Wiwin Windiantina Wintarsih; Neneng Nurastriani; Even Denny Fransisca (Universitas Lampung, 2025)
An insurance policy is a legal contract between the Insurer and the Insured, serving as written proof of their agreement. The Insurer agrees to compensate the Insured for actual losses from damage, loss, or destruction of property—or the loss of interest—caused by an uncertain event. In the perkara a quo, the Plaintiff claimed they still had the right to file against Defendant II for a toll road accident involving Co-Defendant II’s vehicle, despite having already submitted a claim to Co-Defendant II’s insurer. This research uses a qualitative method, analyzing a final and binding court decision (inkracht van gewijsde), with a descriptive-analytical approach. It explores two key questions: (1) How do legal principles of insurance contracts influence dispute resolution? and (2) What is the role of the policy as legal evidence, and how do courts interpret it? A policyholder’s right to claim arises after full premium payment and a covered loss. In this case, the Panel of Judges rejected the Plaintiff’s claim entirely. In the amar putusan, they also rejected the Defendants’ objections, concluding the Plaintiff failed to prove their claim.